Public Policy and Public Service Management: A Bibliometric Mapping of Scientific Research and Emerging Trends - Mutia, Ulmi Sri (LPPPIPublishing, 2025)
This study analyzes the intellectual structure and research evolution in the field of public policy and public service management through a bibliometric approach using data from Scopus between 2019 and 2025. VOSviewer was employed to visualize citation networks, keyword co-occurrence, and thematic developments. The results show a significant increase in publications focusing on governance innovation, digital public services, and citizen participation. The network visualization identifies three major clusters: governance reform, e-government implementation, and performance accountability. The overlay visualization illustrates a shift from traditional bureaucratic models (2019 - 2021) toward digital transformation and sustainable governance (2022 - 2025). The density visualization reveals the dominance of studies originating from Europe and Asia, reflecting global interest in adaptive governance. This research contributes to a deeper understanding of trends and collaboration patterns within the field, offering insights for scholars and policymakers to enhance the effectiveness and inclusivity of public service management.